An acceptance model for contributing factors of continuous intention to use E-learning systems in Oman higher education institutions - Tawafak, Ragad M (2020)
E-learning has become one of the most significant approaches in the educational area. However, e-learning is faced with several problems such as course difficulty, teachersubject knowledge and limited types of technology integration used that affect students’ continuous intention to use e-learning. The success of the e-learning system depends on how the learning takes place, the deployment of factors of support assessment, behaviour intention and student perceptions to be combined for continuous intention to use the elearning system. This research also argues that e-learning systems used to validate learners' learning outcome such as effectiveness, academic performance, student satisfaction, and system use. A review of the literature on the continuous intention to use e-learning systems shows that this area is still in its infancy as many studies focused on assessing e-learning systems from one acceptance model rather than enhancing the combination of factors from many theories of acceptance e-learning models for the continuous intention of use. The purpose of this study is to find the acceptance model of contributing factors that affect the continuous intention to use e-learning systems. This research proposes on merging effectively all e-learning systems outcome to identify the contributing factors for continuous intention to use the e-learning system. Therefore, the main objective of this study is to develop an acceptance model contributing factors for the continuous intention to use the e-learning systems. This study focuses on understanding all influencing factors that related to the continuous use of e-learning system by studying the possible factors used in previous acceptance models such as Technology Acceptance Model (TAM), Task-Technology Fit (TTF) as well as selected Expectation-Confirmation Technology (ECT) and others. To develop the model, factors from TAM, TTF as well as selected ECT factors were combined in the Acceptance Model to the identified independent and dependent factors. An acceptance model was formulated based on the previous model's reviews with dependent and independent factors. To test the model, four (4) Oman universities have been selected as a case study. Data were collected using questionnaires that were returned by 295 undergraduates to assess their feedback on elearning system, after which Partial Least Squares-Structural Equation Modelling (PLSSEM) was employed to evaluate the hypotheses of the developed acceptance model to improve continuous intention to use e-learning system. Results from the survey data show that 12 of 16 hypotheses suggested that the independent and dependent factors are significant for the continuous intention to use e-learning system in higher education institutions. This research reveals the need to develop an acceptance model for contributing factors of continuous intention to use e-learning system for Oman higher education institutions that could be implemented for future enhancement for e-learning models.